Molecular Characterization of Microalgae Thalassiosira sp. Based on Genetic Marker tufA and Potential Test for Bioremediation of Heavy Metal Lead (Pb) - Izzudin, Maulana Zidan; Kusumaningrum, Hermin Pancasakti; Zainuri, Muhammad; Nurhayati, Nurhayati; Jannah, Siti Nur; Wahyuningsih, Candra; Herida, Azalia Puspa; Doktorasaintifika, Heradita Kaniaazzahra (Universitas Diponegoro, 2025)
Heavy metal lead (Pb) pollution in aquatic environments poses a serious threat to aquatic ecosystems and human health. The microalga Thalassiosira sp. has potential as a bioremediation agent for heavy metals; however, further studies are needed to maximize its capability. This study aims to molecularly characterize Thalassiosira sp. using the tufA gene, evaluate the effects of Pb on growth and cell morphology, and assess its Pb uptake efficiency. Methods included DNA isolation, phylogenetic analysis, growth measurement using a hemocytometer, Pb uptake testing via ICP-OES, and cell morphology analysis. Results showed that the tufA gene could molecularly characterize Thalassiosira sp., with a phylogenetic similarity of 99.53% to Conticriba weissflogii (MH571875.1). Pb significantly inhibited growth at concentrations of 0.03 ppm and 0.05 ppm and caused cell aggregation and pigment degradation at higher concentrations (2 ppm). This microalga exhibited the highest Pb uptake efficiency at lower concentrations (0.03–0.05 ppm), reaching 100%, while at 2 ppm, the efficiency decreased to 40%. This study highlights the potential of Thalassiosira sp. in remediating Pb, providing a foundation for the development of microalgae-based biotechnological applications.